Designed CXCR4 mimic acts as a soluble chemokine receptor that blocks atherogenic inflammation by agonist-specific targeting - Christos Kontos (Nature Portfolio, 2020)
The development of specific anti-cytokine/chemokine therapeutic strategies for atherosclerotic disease is challenging. Here, the authors have designed a peptide-based ectodomain mimic of the chemokine receptor CXCR4 that selectively targets MIF but not CXCL12 and blocks experimental atherosclerosis in vivo.